Safety and Pharmacokinetics of Motesanib in Combination with Panitumumab and Gemcitabine-Cisplatin in Patients with Advanced Cancer. (17th March 2011) - Burris, Howard; Stephenson, Joe; Otterson, Gregory A.; Stein, Mark; McGreivy, Jesse; Sun, Yu-Nien; Ingram, Megan; Ye, Yining; Schwartzberg, Lee S.
Abstract : Purpose . The aim of this study was to assess the safety and tolerability of motesanib (an orally administered small-molecule antagonist of vascular endothelial growth factor receptors 1, 2, and 3, platelet-derived growth factor receptor, and Kit) when administered in combination with panitumumab, gemcitabine, and cisplatin. Methods . This was an open-label, multicenter phase 1b study in patients with advanced solid tumors with an ECOG performance status ≤1 and for whom a gemcitabine/cisplatin regimen was indicated. Patients received motesanib (0 mg [control], 50 mg once daily [QD], 75 mg QD, 100 mg QD, 125 mg QD, or 75 mg twice daily [BID]) with panitumumab (9 mg/kg), gemcitabine (1250 mg/m 2 ) and cisplatin (75 mg/m 2 ) in 21-day cycles. The primary endpoint was the incidence of dose-limiting toxicities (DLTs). Results . Forty-one patients were enrolled and received treatment (including 8 control patients). One of eight patients in the 50 mg QD cohort and 5/11 patients in the 125 mg QD cohort experienced DLTs. The maximum tolerated dose was established as 100 mg QD. Among patients who received motesanib (n = 33 ), 29 had motesanib-related adverse events. Fourteen patients had serious motesanib-related events. Ten patients had motesanib-related venous thromboembolic events and three had motesanib-related arterial thromboembolic events, two of which were considered serious. One patient had a complete response and nine had partial responses as their best objective response. Conclusions . The combination of motesanib, panitumumab, and gemcitabine/cisplatin could not be administered consistently and, at the described doses and schedule, may be intolerable. However, encouraging antitumor activity was noted in some cases.